Transoral robotic total laryngectomy: Report of 3 cases. Issue 11 (8th March 2013) - Dowthwaite, Samuel; Nichols, Anthony C; Yoo, John; Smith, Richard V.; Dhaliwal, Sandeep; Basmaji, John; Franklin, Jason H.; Fung, Kevin
<x xml:space="preserve">Abstract</x> Background Because of the significant toxicity of chemoradiation regimens, there has been a resurgence of interest in the primary surgical management of head and neck cancer and, in particular, the use of minimally invasive surgery. One such technique is transoral robotic surgery (TORS). We aim to discuss the potential role of TORS in patients requiring total laryngectomy (TL). Methods and Results Three patients underwent TORS‐assisted narrow‐field TL. Relative data on preoperative, intraoperative, and postoperative management were collated including postoperative complications. Conclusions We present 3 cases of transoral robotic surgery (TORS)–assisted TL in patients requiring narrow field laryngectomy without requirement for neck dissection. In reviewing these cases we provide a discussion of pertinent preoperative and intraoperative considerations that can assist in facilitating successful completion of the procedure. In particular, appropriate assessment at the pinsertlinePOLA_Del_Blank_PgPOLA_Shift_FramePORT_rem_fpg_underremovelinetabminilanning endoscopy in addition to a methodical surgical approach are vital to the successful use of the robot in TORS‐assisted TL. © 2013 Wiley Periodicals, Inc. Head Neck, 35: E338–E342, 2013